Analysis of Drug use in Participants of the Kartini Madu II Elderly Posyandu, Kartini Surya Khatulistiwa Institution, East Pontianak - Milenia Fara Endira; Syarifah Nurul Yanti R.S.A; Nurmainah Nurmainah (Sean Institute, 2025)
There is a decline in body abilities and a decline in physiological functions. Increased use of drugs used by the elderly can increase the risk of drug-related problems. This study aims to analyze drug use in the elderly at the Kartini Madu II Elderly Health Post, Kartini Surya Khatulistiwa Institution, Pontianak in 2019. This descriptive analytical study with a cross-sectional design involved 55 elderly patients who met the inclusion criteria. The results showed that the majority of patients were women (87.3%) with the largest age range between 60-69 years (65.4%). The most common complaints were dizziness, itching, and coughing. The most commonly used types of drugs were mefenamic acid, captopril, and paracetamol. This study also found that there were drugs that did not meet the STOPP criteria (diclofenac sodium and CTM) and START (kalk and captopril). The results of this study can be used as a reference to improve the rational use of drugs in the elderly.